Assessment of nervous-muscular system's potentials of cyclic kinds of sports sportsmen - I.V. Skladanivska (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Purpose: to work out and substantiate methodic of assessment of nervous-muscular system's potentials of elite sportsmen, representatives of cyclic kinds of sports. Material: in the research sportsmen of cyclic kinds of sports (n = 28) participated. Testing was conducted with the help of ergometer of bicycle type. Results: we present methodic of assessment of nervous-muscular system's potentials of elite sportsmen with the help of surface electromyography. It was found that sportsmen with high aerobic potentials reach second electromyography threshold with power of work, corresponding, in average, 80.5% VO2 max. We also found confident correlation (r=0.59, р≤0.05) between maximal concentration of blood lactate and maximal amplitude of electromyogram. Conclusions: application of our approaches permits to assess reserve potential by type of muscle fibers, which influence on sportsman's bent to certain kind of motor functioning. The worked out assessment system permits to determine contribution of different motor units' types in achievement of required parameters of work.